1998
DOI: 10.1002/(sici)1097-4636(199810)42:1<1::aid-jbm1>3.3.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of bacterial adherence to a high‐water‐content polymer by a water‐soluble, nonsteroidal, anti‐inflammatory drug

Abstract: Deposition and aggregation of lachrymal proteins on the contact lens surface can promote bacterial adherence. Lysozyme is the major tear protein and is also mainly responsible for the formation of protein deposits on contact lenses. Nonsteroidal anti-inflammatory drugs (NSAID) prevent protein aggregation. The effect of a watersoluble NSAID drug on bacterial adherence to high-watercontent/ionic disposable contact lenses was examined in a radiolabeling study. Dose-related inhibition of adherence of Staphylococcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…9 Elucidation of the adhesive mechanisms of clinical strains may help in developing antiadhesive coatings or anti-adhesin drugs. 18,19 The production of PIA by this species is mediated by the ica operon.…”
Section: Discussionmentioning
confidence: 99%
“…9 Elucidation of the adhesive mechanisms of clinical strains may help in developing antiadhesive coatings or anti-adhesin drugs. 18,19 The production of PIA by this species is mediated by the ica operon.…”
Section: Discussionmentioning
confidence: 99%
“…Salicylates and other nonsteroidal anti-inflammatory drugs are known to prevent bacterial adhesion on medical devices (Arciola, Montanaro, Caramazza, Sassoli, & Cavedagna, 1998). Rosenberg et al found that the S. Typhimurium strain MAE52, which normally forms pellicles at the air-liquid interface, does not form pellicles when it was grown in growth medium containing a glass coverslip coated with a salicylate-based poly(anhdride ester) from which salicylic acid is released via surface erosion, while the planktonic growth of the bacteria is not reduced (Rosenberg, Carbone, Römling, Uhrich, & Chikindas, 2008).…”
Section: Biofilm-specific Inhibitors: Top-downmentioning
confidence: 99%
“…Coating the catheter with acetylsalicylic acid or sodium salicylate reduces or inhibits microbial adherence, Bandazac lysine (non steroidal anti-inflammatory) was found to prevented the adherence of bacteria to contact lenses (Arciola et al, 1998).…”
Section: B Non-antimicrobial Agentsmentioning
confidence: 99%